Association of serum vascular endothelial growth factor-C, vascular endothelial growth factor receptor-3, and insulin-like growth factor 1 levels with metastasis and prognosis in patients with nasopharyngeal carcinoma - Li, Yongchun; Wang, Le; Zhao, Yutong; Zhao, Jia; Wen, Wulin (Frontiers in Oncology, 2025)
ObjectiveTo investigate the association of serum levels of Vascular Endothelial Growth Factor-C (VEGFC), Vascular Endothelial Growth Factor Receptor-3 (VEGFR-3), and Insulin-like Growth Factor 1 (IGF1) with metastasis and prognosis in patients with nasopharyngeal carcinoma (NPC).MethodsThis retrospective study included 298 patients diagnosed with NPC at our institution between January 2022 and December 2023. Patients were categorized based on the presence of metastasis at diagnosis or during follow-up into a metastatic group (n=78) and a non-metastatic group (n=220). Clinical data, including plasma Epstein-Barr virus (EBV) DNA load, were collected, and serum VEGFC, VEGFR-3, and IGF1 levels were measured. Patients were followed up for a mean of (12.02 ± 1.21) months (minimum 12 months). Univariate and multivariate logistic regression analyses were performed to identify factors influencing NPC metastasis. Receiver Operating Characteristic (ROC) curve analysis was used to evaluate the predictive value of these biomarkers for NPC metastasis. Kaplan-Meier survival analysis and log-rank tests were used to evaluate the prognostic value of the biomarkers for OS.ResultsSerum levels of VEGFC, VEGFR-3, and IGF1 were significantly higher in the metastatic group compared to the non-metastatic group (P<0.05). Similarly, these markers were significantly elevated in patients with poor prognosis compared to those with good prognosis (P<0.05). Multivariate logistic regression analysis identified advanced T stage, N stage, high plasma EBV DNA load, and elevated serum VEGFC, VEGFR-3, and IGF1 levels as independent risk factors for NPC metastasis. Combined detection of serum VEGFC, VEGFR-3, and IGF1 yielded a significantly higher Area Under the Curve (AUC) for predicting NPC metastasis than individual markers, and a nomogram incorporating all independent risk factors showed excellent predictive performance (C-index: 0.941). Kaplan-Meier analysis revealed that patients with high levels of VEGFC, VEGFR-3, IGF1, or a high-risk score from the combined biomarker model had significantly poorer OS (all P<0.001).ConclusionSerum levels of VEGFC, VEGFR-3, and IGF1 are significantly correlated with metastasis and poor prognosis in NPC patients. These biomarkers, particularly when combined and integrated with EBV DNA load, serve as valuable indicators for predicting metastatic risk and assessing survival outcomes in NPC.